Introduction into Practice Methods of Early Diagnostics in Diseases of the Cervic (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Cervical cancer (CC) is considered to be one of some oncological diseases, which, when diagnosed at an early stage, can be effectively treated, which increases overall and recurrence-free survival, improves the quality of life of patients, and reduces the cost of treatment. The cause of cervical cancer is the human papillomavirus (HPV) of oncogenicgenotypes, which can be prevented by screening tests.